Short gastrocnemius: epidemiology and associated signs and symptoms - Machado, Samuel; Hardt, Marcelo Rassweiler; Demore, André Bergamaschi; Kim, Antônio; Camargo, Leandro Marcantonio; Barbosa, Carolina Claudino (Scientific Journal of the Foot & Ankle, 2018)
Objective: To determine the prevalence of short gastrocnemius in orthopaedic patients treated in the emergency room and the foot and ankle outpatient clinic of a public hospital and to evaluate the relationship between prevalence and certain specific symptoms. Methods: This was an observational cross-sectional study conducted using a questionnaire completed by patients treated in February 2018. Results: Of the 160 patients studied, 21 (13.1%) had a diagnosis of shortening of the gastrocnemius. The condition was more prevalent in females than in males, with no differences in race, age, laterality or occupation. The most commonly associated symptoms were calf pain, back pain, equinism and metatarsalgia, which were all present in more than 2/3 of cases. Conclusion: Shortening of the gastrocnemius is a fairly common pathology that deserves greater attention in orthopaedic practice. Additional studies are needed to better correlate epidemiological findings with this pathology. Level of Evidence II; Diagnostics Studies.